Informational Supervision Approach as an Effort to Improve the Quality of Learning in Schools - Zakiya, Nabila; Simatupang, Umy Nadrah; Aulia, Yenni; Marsidin, Sufyarma; Rifma, Rifma (International Journal of Educational Dynamics, 2023)
collaboration in order to educate the nation's children. The elements contained in it are also inseparable from the components which are considered as something very important in supporting effectiveness and quality. The role of the principal is very close to quality improvement by taking responsibility as a supervisor. Sri Banum Muslim (2013: 38) summarizes supervision "supervision is assistance in the development of a better teaching learning situation". Regarding the scope of the summary, supervision services cover all aspects, including teachers, methods, techniques, materials and objectives. Based on the literature study from previous research, the researchers found that the decline in the quality of learning was likely due to factors based on the ineffective implementation of supervision in schools, so that the implementation of learning became less effective. One of the supervision approaches that can be carried out by school principals and supervisors in order to improve teacher professionalism is the informational supervision approach.